2020
DOI: 10.1186/s12964-020-00646-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical Fzd7 signaling contributes to breast cancer mesenchymal-like stemness involving Col6a1

Abstract: Mesenchymal-like stemness is characterized by epithelial-mesenchymal transition (EMT). Breast cancer (BC) cell mesenchymal-like stemness is responsible for distal lung metastasis. Interrogation of databases showed that Fzd7 was closely associated with a panel of mesenchymal-related genes and a panel of stemness-related genes. Fzd7 knockdown in mesenchymal-like MDA-MB-231 and Hs578T cells reduced expression of Vimentin, Slug and Zeb1, induced an epithelial-like morphology, inhibited cell motility, impaired mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In contrast, fluorescence recovery after photobleaching (FRAP) revealed that WNT5B did not affect FZD6 mobility, suggesting a lack of WNT5B-FZD6 interactions, at least in the HEK293T model system ( Kilander et al, 2014 ). In silico analysis predicts that FZD8 has the highest affinity ( Agostino et al, 2017 ; Dahiya et al, 2019 ), while in vitro and in vivo studies show that WNT5B can bind to FZD1 ( Park et al, 2015 ), FZD2 ( van Dijk et al, 2016 ), FZD4 ( Mazzotta et al, 2016 ; Sarin et al, 2018 ), FZD5 ( Sarin et al, 2018 ), FZD6 ( Katanaev and Buestorf, 2009 ; Mazzotta et al, 2016 ), and FZD7 ( Yin et al, 2020 ).…”
Section: Wnt5b Activity and Signalingmentioning
confidence: 99%
“…In contrast, fluorescence recovery after photobleaching (FRAP) revealed that WNT5B did not affect FZD6 mobility, suggesting a lack of WNT5B-FZD6 interactions, at least in the HEK293T model system ( Kilander et al, 2014 ). In silico analysis predicts that FZD8 has the highest affinity ( Agostino et al, 2017 ; Dahiya et al, 2019 ), while in vitro and in vivo studies show that WNT5B can bind to FZD1 ( Park et al, 2015 ), FZD2 ( van Dijk et al, 2016 ), FZD4 ( Mazzotta et al, 2016 ; Sarin et al, 2018 ), FZD5 ( Sarin et al, 2018 ), FZD6 ( Katanaev and Buestorf, 2009 ; Mazzotta et al, 2016 ), and FZD7 ( Yin et al, 2020 ).…”
Section: Wnt5b Activity and Signalingmentioning
confidence: 99%
“…In ovarian cancer, FZD7 expression correlated with resistance to platinum-based chemotherapy, tumor initiation, and cancer stem cell (CSC) proliferation (55,56). In additional examples, FZD7 was associated with epithelial-mesenchymal transition in triple-negative breast cancer (57), cisplatin and paclitaxel resistance in uterine cancer (58), and tumor proliferation in on October 24, 2021. © 2021 American Association for Cancer Research.…”
Section: Discussionmentioning
confidence: 99%
“…Since the end of 1970s, its incidence ranks the first place of female tumors, and it increases by 2% per year [ 19 ]. Advanced breast cancer is prone to distal metastasis, which greatly increases the difficulty of treatment [ 20 ]. Conventional surgical resection and chemoradiotherapy have little effect on breast cancer with high metastasis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%